Peranan Pupuk Organik Kascing Untuk Mendukung Program KRPL Di KWT Melati Kelurahan Bandungrejosari Kecamatan Sukun Kota Malang - Jalu Lokha; Dwi Purnomo; Bambang Sudarmanto; Very Tubagus Irianto (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2021)
Organic fertilizer comes from dead plants, animal impurities, and organic waste that has gone through the process of engineering. Kascing is a solid organic fertilizer derived from the process of vermicompost assisted by the role of Earthworm (Lumbricus rubellus). The purpose of this research is to know the content of kascing by conducting laboratory tests and know the dose of kascing for increasing the production of Pakcoy by conducting experimental design. The research was conducted on campus Politeknik Pembangunan Pertanian Malang using Randomized Block Design (RBD). Data analysis is processed using Analysis of Varience (ANOVA) with a level of 5%, and followed by a test Duncan Multiple Range Test (DMRT) if there is a real difference with the level of 5%. Laboratory test results showed C-organic content: 35.43%, C/N ratio: 23.16, N: 1.53%, P2O5:2.94%, and K2O: 0.60%. Experimental design of the influence of kascing at a dose of 0 g, 300 g, 400 g, 500 g, 600 g, and 700 g of Pakcoy gave a different result in the high parameters of plants, the number of leaves, and the fresh weight of Pakcoy. While the parameters of pakcoy roots give no different results.